Preeclampsia induced by STOX1 overexpression in mice induces intrauterine growth restriction, abnormal ultrasonography and BOLD MRI signatures. Issue 6 (June 2018) - Collinot, Hélène; Marchiol, Carmen; Lagoutte, Isabelle; Lager, Franck; Siauve, Nathalie; Autret, Gwennhael; Balvay, Daniel; Renault, Gilles; Salomon, Laurent J.; Vaiman, Daniel
Abstract : Background: Preeclampsia is a major hypertensive disease caused by pregnancy, inducing proteinuria and increased blood pressure starting from the second half of pregnancy (early preeclampsia) or near the end of pregnancy (late preeclampsia). Pre-symptomatic diagnosis would allow for therapeutic interventions, such as with low-dose aspirin. Among non-invasive methods to explore organ physiology, Doppler ultrasonography (US) and functional blood oxygenation level-dependent (BOLD) MRI (which do not need radioactive contrast agents such as gadolinium) can be used in pregnant women. Methods: In this study, we used US and BOLD MRI to finely characterize the phenotype of preeclampsia induced by the foeto-placental overexpression of the transcription factor storkhead box 1A (STOX1A) in female mice. Results: We could observe late fetal growth restriction consistent with the placental dysfunction revealed by US and the known association between preeclampsia and intra-uterine growth restriction. On US, uterine and umbilical artery as well as heart and kidney parameters were modified in preeclamptic mice. On BOLD MRI, mean T2* values revealed considerable differences between control and preeclamptic placentas, which suggests altered dynamics of oxygen release and ratio of oxyhemoglobin to deoxyhemoglobin in the model. Conclusion: These preliminary pre-clinical results suggest that BOLD MRI could be evaluated as a prognostic/diagnostic tool for preeclampsia. Abstract : Supplemental Digital Content is available in the text